Tiller dynamics on elephantgrass under postgrazing stubble heights influence - Carvalho, Carlos Augusto Brandão de; Paciullo, Domingos Sávio Campos; Rossiello, Roberto Oscar Pereyra; Deresz, Fermino (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to evaluate the effects of two stubble heights (50 and 100 cm) on tiller dynamics, dry mass for tiller and dry mass herbage accumulation of basal and aerial tillers in elephantgrass pastures managed under grazing. A complete randomized block design with split plot arrangement and four replications were used. The stubble heights did not influence the population density, tiller mortality and birth percentage, dry mass per tiller and herbage accumulation of basal and aerial tillers. Basal and aerial tillers showed increase of 47% and reduction of 16% on population density between spring and summer, respectively. Tillers with leaves were 92% of aerial tillers and 52% of basal tillers. Tiller birth percentage was the highest determinant of population density variations. The dry mass herbage accumulation was larger for basal tillers during spring, and the aerial tillers increased it during summer.